Doctors commitment and long-term effectiveness for cost containment policies: lesson learned from biosimilar drugs - Menditto E; Orlando V; Coretti S; Putignano D; Fiorentino D; Ruggeri M (Dove Medical Press, 2015)
Enrica Menditto,1 Valentina Orlando,1 Silvia Coretti,2 Daria Putignano,1 Denise Fiorentino,1 Matteo Ruggeri2 1CIRFF, Center of Pharmacoeconomics, Federico II University of Naples, Naples, 2Postgraduate School of Health Economics and Management (ALTEMS), Università Cattolica del Sacro Cuore, School of Economics, Rome, Italy Background: Agency is a pervasive feature of the health care market, with doctors acting as agents for both patients and the health care system. In a context of scarce resources, doctors are required to take opportunity cost into account when prescribing treatments, while cost containment policies cannot overlook their active role in determining health care resource allocation. This paper addresses this issue, investigating the effects of cost containment measures in the market of biosimilar drugs that represent a viable and cost-saving strategy for the reduction of health care expenditure. The analysis focuses on a particular region in Italy, where several timely policies to incentivize biosimilar prescribing were launched. Methods: Drugs were identified by the anatomical therapeutic chemical classification system. Information about biosimilar drugs and their originator biological products was extracted from the IMS Health regional database. Drug consumption was expressed in terms of counting units, while expenditure was evaluated in Euro (€).The market penetration of biosimilars was analyzed by year and quarterly. Results: In the Campania region of Italy, the effects of cost containment policies, launched between 2009 and 2013, showed the prescription of biosimilars strongly increasing in 2010 until prescribing levels reached and exceeded the market share of the reference biological products in 2012. After a slight reduction, a plateau was observed at the beginning of 2013. At the same time, the use of the originator products had been decreasing until the first quarter of 2011. However, after a 1-year plateau, this trend was reversed, with a new increase in the consumption of the originators observed. Conclusion: Results show that the cost containment policies, applied to cut health expenditure "to cure and not to care", did not produce the cultural change necessary to make these policies effective in the long run. Therefore, top-down policies for cost containment are not successful; rather, a bottom-up approach based on consensus among professionals should become the preferred option. Keywords: cost containment policy, biosimilar drugs, health care expenditure, policy making